P12.04.A Exosomes from glioma associated sphere forming cells induce a transition of invasive phenotype via transfer of EMP2 and CA9. (5th September 2022) - Kang, S; Ryu, B; Sa, J; Kim, H; Park, K; Yu, S; Hong, D; Kim, K
Abstract: Background: Glioblastoma multiforme (GBM) mostly occurs local recurrence at normal parenchyme adjacent tumor despite of conventional treatment. Glioma stem like cells (GSC) forming intratumoral heterogeneity within the GBM acquired the microenvironmental adaptation by inter-exosomal contents exchange between heterogenic cells. In addition, GSC has an invasive potential as like human GBM. Therefore, we investigate whether exosomal proteins of GSC affect the normal tissue invasion in GBM. Material and Methods: Exosomes were isolated by Size-Exclusion method from conditioned media and validated by Electron microscope and Immunoblot assay. Exosomal proteomics were examined with Liquid Chromatography-Mass Spectrometry (LC/MS). To produce the fluorescent exosome, bi-cistron vectors were cloned with shRNA and CD63-GFP. To identify the effect of tranfected exosome, the isolated exosomes were treated to recipient cells and examined the invasion by 3D invasion assay and mouse intracranial model. Results: Firstly, we dichotomized two groups following tumor invasion at matrigel assay and GSC derived orthotopic mouse model. CSC2 and X01 GSCs revealed highly invasive phenotype whereas 83NS and 528NS GSCs did not. Exosome was isolated in each group and identified by CD63 expression or electron microscopy. In proteomics analysis, hypoxia, extracellular matrix organization, GTPase cycle related proteins were enriched in highly invasive cell's exosome. Among them, we focused the carbonic anhydrase IX (CA9) and the epithelial membrane protein 2 (EMP2) on its permissive role to glioblastoma invasion respectively. CA9 and EMP2 mRNA and protein levels were verified in GSCs and their exosomes and the high expression levels were detected in CSC2 and X01 compared to the low one in 83NS and 528NS GSCs. To evaluate the effects of CA9 and EMP2 on exosome mediated invasion potential, viral bi-cistron vectors was composed with the target gene knockdown and the CD63 fluorescence was used to detect intracellular exosome transfer. Interestingly, the decreased expression of phosphorylated FAK, a key invasive marker, was observed after Lentiviral mediated CA9- and EMP2-knockdown in highly invasive CSC2. To identify whether CA9 and EMP2 proteins are the intracellular effector protein responsible for exosome mediated glioma invasion, the donor exosomes (Exo-CSC2-sh-CA9 and Exo-CSC2-EMP2, after Lentiviral transfection to CSC2s) were isolated and treated to the non invasive 528NS cells as recipient cells. In 3D invasion assay, Exo-CSC2-shCA9 or Exo-CSC2-shEMP2 mediated tumor invasion was significantly decreased at 528NS GSCs compared to Exo-CSC2-shEV. These features were found at mouse intracranial model as well. Conclusion: Together with these, we conclude that exosome derived from GSCs induces a transition of invasive phenotype via transfer of EMP2 and CA9 proteins.